Comparative Efficacy of Collaborative, Cooperative, and Traditional Learning on Linier Algebra Problem-Solving Ability in Higher Education - Dewi Nurmalitasari; Tatang Herman; Sufyani Prabawanto; Jarnawi Afgani Dahlan (Mosharafa: Jurnal Pendidikan Matematika, 2025)
Tantangan yang dihadapi siswa dalam memahami sistem persamaan linear berasal dari sifat abstrak subjek dan perhitungan ekstensif yang diperlukan untuk matriks berordo lebih dari tiga. Studi kuasi-eksperimental ini meneliti efektivitas komparatif model pembelajaran kolaboratif dan kooperatif dalam meningkatkan kemampuan pemecahan masalah matematika mahasiswa S1 pada sistem persamaan linear. Partisipan terdiri dari tiga kelas utuh: dua kelompok eksperimen mahasiswa Ilmu Komputer (tahun akademik 2024/2025) yang diajar menggunakan model pembelajaran kolaboratif dan model pembelajaran kooperatif, dan satu kelompok kontrol mahasiswa Pendidikan Matematika (tahun akademik 2021/2022) yang menerima pengajaran tradisional. Sebelum intervensi, tes pendahuluan diberikan untuk memeriksa kemampuan pemecahan masalah dasar. ANOVA satu arah kemampuan awal yang tidak sama. Oleh karena itu, efektivitas pembelajaran dievaluasi menggunakan skor normalized gain. Kelompok pembelajaran kolaboratif mencapai rata-rata N-Gain tertinggi, diikuti oleh kelompok pembelajaran kooperatif, sedangkan kelompok pembelajaran tradisional menunjukkan peningkatan terendah. Hasil ini menunjukkan bahwa pembelajaran kolaboratif terstruktur lebih efektif dalam meningkatkan kemampuan pemecahan masalah siswa dalam sistem persamaan linear dibandingkan dengan pendekatan kooperatif dan tradisional. The challenges students face in comprehending systems of linear equations originate from the abstract character of the subject and the extensive calculations required for matrices of order more than three. This quasi-experimental study investigated the comparative effectiveness of collaborative and cooperative learning models in improving undergraduate students’ mathematical problem-solving ability on systems of linear equations. The participants consisted of three intact classes: two experimental groups of Computer Science students (academic year 2024/2025) taught using a collaborative learning model and a cooperative learning model, respectively, and one control group of Mathematics Education students (academic year 2021/2022) receiving traditional instruction. Prior to the intervention, a pre-test was administered to examine baseline problem-solving ability. One-way ANOVA indicating unequal initial ability. Therefore, learning effectiveness was evaluated using normalized gain. Post-test scores were analyzed descriptively, as their distribution violated normality assumptions. The collaborative learning group achieved the highest mean N-Gain, followed by the cooperative learning group, while the traditional learning group demonstrated the lowest improvement. These results suggest that structured collaborative learning is more effective in enhancing students’ problem-solving improvement in systems of linear equations than cooperative and traditional approaches.